Association of CD33 and MS4A cluster variants with Alzheimer's disease in East Asian populations. (16th November 2015) - Mao, Yan-Fang; Guo, Zhang-Yu; Pu, Jia-Li; Chen, Yan-Xing; Zhang, Bao-Rong
Highlights: CD33 polymorphisms are associated with late-onset Alzheimer's disease (LOAD) in East Asia. The G allele of the single nucleotide polymorphism rs3826656 is a risk factor for LOAD. MS4A cluster polymorphisms are associated with LOAD in East Asian populations. The rs610932 variant protects against LOAD in East Asian populations. Abstract: CD33 and MS4A cluster variants have been identified to modulate the risk of Alzheimer's disease (AD) in several recent genome-wide association studies (GWAS) in Caucasians. In the present study, we first conducted a case-control study to investigate the CD33 single nucleotide polymorphisms (SNPs) rs3865444 and rs3826656 and the MS4A cluster SNPs rs610932 and rs670139 in a cohort from eastern China that comprised 126 late-onset Alzheimer's disease (LOAD) patients and 129 healthy controls. The results revealed that the frequency of rs3826656 major (G) allele carriers was higher among the LOAD patients than among the controls [ P = 0.005; odds ratio (OR), 1.760; 95% confidence interval (CI), 1.185–2.615]. In apolipoprotein E ( APOE ) ε4 allele carriers, the G allele of the SNP rs3865444 was found to be associated with an increased risk of LOAD ( P = 0.002; OR, 3.391; 95% CI, 1.512–7.605). Next, we re-evaluated the association between these variants and LOAD by conducting a meta-analysis using data from studies of East Asian populations, including the present case-control study, and confirmed that rs3826656 increased the risk of LOAD. In addition, we identified a significant association between rs610932 and LOAD ( P = 0.035; OR, 0.79; 95% CI, 0.63–0.98). Note that heterogeneity should be considered during the interpretation of these results; significant heterogeneity was identified among studies on rs3865444, even in a subgroup analysis based on stratification of studies by the country of origin. In summary, our results suggest that CD33 and MS4A cluster variants are associated with LOAD susceptibility in East Asian populations.